The effect of day-neutral mutations in barley and wheat on the interaction between photoperiod and vernalization - Turner, Adrian S. (Springer Berlin Heidelberg, 2013)
Vernalization-2 (Vrn-2) is the major flowering repressor in temperate cereals. It is only expressed under long days in wild-type plants. We used two day-neutral (photoperiod insensitive) mutations that allow rapid flowering in short or long days to investigate the day length control of Vrn-2. The barley (Hordeum vulgare) early maturity8 (eam8) mutation affects the barley ELF3 gene. eam8 mutants disrupt the circadian clock resulting in elevated expression of Ppd-H1 and the floral activator HvFT1 under short or long days. When eam8 was crossed into a genetic background with a vernalization requirement Vrn-2 was expressed under all photoperiods and the early flowering phenotype was partially repressed in unvernalized (UV) plants, likely due to competition between the constitutively active photoperiod pathway and the repressing effect of Vrn-2. We also investigated the wheat (Triticum aestivum) Ppd-D1a mutation. This differs from eam8 in causing elevated levels of Ppd-1 and TaFT1 expression without affecting the circadian clock. We used genotypes that differed in “short-day vernalization”. Short days were effective in promoting flowering in individuals wild type at Ppd-D1, but not in individuals that carry the Ppd-D1a mutation. The latter showed Vrn-2 expression in short days. In summary, eam8 and Ppd-D1a mimic long days in terms of photoperiod response, causing Vrn-2 to become aberrantly expressed (in short days). As Ppd-D1a does not affect the circadian clock, this also shows that clock regulation of Vrn-2 operates indirectly through one or more downstream genes, one of which may be Ppd-1. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00122-013-2133-6) contains supplementary material, which is available to authorized users.